Pendampingan Peningkatan Nilai-Nilai Anti Korupsi pada Pemuda Orang Asli Papua di Era Otonomi Khusus - Rudini Hasyim Rado; Adi Sumarsono; Muhammad Saiful Fahmi; Restu Monika Nia Betaubun (JURNAL PENGABDIAN MASYARAKAT INDONESIA, 2025)
It cannot be denied that the onslaught of consumptive lifestyle changes due to the existence of Special Autonomy funds has the potential to cause corrupt behaviour. In fact, it could result in the failure to achieve development goals and improvements in the quality of life in the Papua region. To ensure that Otsus is not merely a fleeting ‘euphoria,’ mitigation efforts are necessary, including legal education initiatives aimed at instilling anti-corruption values among the indigenous youth of Papua (OAP) during the Special Autonomy (Otsus) era. The implementation of this service activity uses a socialisation/education method with techniques such as lectures, case studies, educational videos, discussions, and evaluations. The results of this service activity received positive feedback and responses from the OAP youth as the future leaders. The understanding of corruption prevention based on the integration of anti-corruption values as a strategic step in shaping culturally aware and legally conscious OAP youth begins from the family environment to the surrounding community, especially considering that the impact of corruption can hinder development in the Otsus era. Based on the results obtained after evaluation, there was a significant increase in knowledge of anti-corruption values.